Plio-Pleistocene rapid uplift process of the Nepal Himalaya revealed from fission-track ages - Arita, Kazunori; Ohira, Hiroto (Himalayan Journal of Sciences, 2008)
Himalayan Journal of Sciences Vol.2(4) Special Issue 2004 pp. 98-99